Evaluating antenatal breastmilk expression outcomes: a scoping review - Foudil-Bey, Imane; Murphy, Malia S. Q.; Dunn, Sandra; Keely, Erin J.; El-Chaâr, Darine (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Antenatal breastmilk expression (aBME) is recommended by some healthcare providers to improve lactation, breastfeeding, and newborn outcomes, particularly for women with diabetes as they face unique challenges with breastfeeding. However, there is limited evidence of the potential harms and benefits of this practice. Our objective was to conduct a scoping review to map the literature describing maternal and newborn outcomes of aBME. Methods We searched Medline, Embase, CINAHL, Cochrane Database of Systematic Reviews, British Library E-Theses Online Services (EThOS) database, OpenGrey, and Clinical trials.gov from inception to January 2020. Studies in English that reported on the effect of aBME on maternal and newborn outcomes, and the experiences of women who have engaged in the practice were included for screening. Titles, abstracts, and full-text articles were screened by two independent reviewers. A critical appraisal and clinical consultation were conducted. Key findings were extracted and summarized. Results We screened 659 studies and 20 met the inclusion criteria. The majority of included studies (n = 11, 55.0%) were published after 2015, and seven (35.0%) originated from Australia. Ten (50.0%) studies provided data on high-risk obstetrical populations, including those with diabetes (n = 8), overweight or obesity (n = 1), and preeclampsia (n = 1). Commonly reported outcomes included breastfeeding status at discharge or follow-up, mode of delivery, newborn blood glucose, and time to establishing full lactation. Maternal experiences were related to challenges with aBME, confidence and mastery, perceived impact, security and altruism, learning and resources, and physical symptoms as a result of aBME. The critical appraisal demonstrated limited high-quality evidence surrounding aBME. Conclusions Our findings demonstrate increasing interest in the safety, efficacy, and acceptability of aBME. Existing studies are heterogenous with variable research questions, outcomes, study designs, and methodology. The recommendations made in this review can be used to help inform  future studies evaluating aBME.